2006
DOI: 10.1038/sj.cr.7310007
|View full text |Cite
|
Sign up to set email alerts
|

The role of NBS1 in DNA double strand break repair, telomere stability, and cell cycle checkpoint control

Abstract: The genomes of eukaryotic cells are under continuous assault by environmental agents and endogenous metabolic byproducts. Damage induced in DNA usually leads to a cascade of cellular events, the DNA damage response. Failure of the DNA damage response can lead to development of malignancy by reducing the efficiency and fidelity of DNA repair. The NBS1 protein is a component of the MRE11/RAD50/NBS1 complex (MRN) that plays a critical role in the cellular response to DNA damage and the maintenance of chromosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 109 publications
(174 reference statements)
1
63
0
2
Order By: Relevance
“…The central importance of ATR and ATM is underscored by human diseases such as ataxia telangiectasia, which result from mutation of these genes. More recently the MRE11, RAD50, NBS1 (MRN) complex has been demonstrated to function early in the DNA damage response together with the ATM and ATR kinases, and mutations in MRN genes have been linked to the diseases Nijmegen breakage syndrome (NBS) and ataxia telangiectasia-like disorder (Uziel et al 2003;Difilippantonio et al 2005;Lee and Paull 2005;Stiff et al 2005;You et al 2005;Jazayeri et al 2006; for review see Abraham and Tibbetts 2005;Stavridi and Halazonetis 2005;Zhang et al 2006). 1 The MRN complex has roles in cell cycle checkpoint signaling as well as in DNA repair and telomere maintenance (for review see D'Amours and Jackson 2002; Zhang et al 2006).…”
Section: Mre11mentioning
confidence: 99%
“…The central importance of ATR and ATM is underscored by human diseases such as ataxia telangiectasia, which result from mutation of these genes. More recently the MRE11, RAD50, NBS1 (MRN) complex has been demonstrated to function early in the DNA damage response together with the ATM and ATR kinases, and mutations in MRN genes have been linked to the diseases Nijmegen breakage syndrome (NBS) and ataxia telangiectasia-like disorder (Uziel et al 2003;Difilippantonio et al 2005;Lee and Paull 2005;Stiff et al 2005;You et al 2005;Jazayeri et al 2006; for review see Abraham and Tibbetts 2005;Stavridi and Halazonetis 2005;Zhang et al 2006). 1 The MRN complex has roles in cell cycle checkpoint signaling as well as in DNA repair and telomere maintenance (for review see D'Amours and Jackson 2002; Zhang et al 2006).…”
Section: Mre11mentioning
confidence: 99%
“…Mutations in NBS1 significantly downregulate MRN complex expression and markedly disrupt its function, thus enhancing cisplatin-induced DNA damage and cytotoxicity (Tran et al, 2004;Araki et al, 2010). Studies in mice have indicated that heterozygous for NBS1-null mutations develop tumors in lung, liver, mammary gland and prostate (Dumon-Jones et al, 2003;Zhang et al, 2006). NBS1 overexpression has been observed in several smoking-related cancer sites including NSCLC, hepatoma, esophageal cancer and head and neck squamous cell carcinoma (HNSCC) (Chen, 2005;Yang, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The NBS1 gene encompasses 48797 bps of genomic sequence on chromosome 8q21 with about 48 single nucleotide polymorphisms (SNPs) according to the National Center for Biotechnology Information dbSNPs public databases (Zhang et al, 2006). Rs1805794 located in exon 5 of NBS1 is one of the most common polymorphisms and can induce an amino acid substitution from Glu to Gln.…”
Section: Introductionmentioning
confidence: 99%
“…While each protein has unique characteristics, the complex functions as a whole in cellular processes such as DNA replication, DNA repair, cell cycle regulation and telomere maintenance (reviewed in refs. [26][27][28]. The MRN complex has been proposed to be a sensor of DNA damage, 29,30 and is known to be necessary for full activation of the ATM and ATR kinases [31][32][33][34][35][36][37][38][39][40] (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%